Management of postpartum reproduction in crossbred cows with Dinoprost - SINHA, V K; SINGH, BALRAJ; SINHA, A K (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 32 cows belonging to different small private farms around Ranchi. ’Dinoprost’ 25 mg was administered intramuscularly to each of 20 cows within 6 hrs of parturition and 12 cows were kept as control. The incidence of retention offetal membranes in ’Dinoprost’ treated cows was significantly (P<0.05) lower than the control. There was no significant difference with respect to reduction in diameter of cervix and uterine corona between ’Dinoprost’ treated and control groups at day 10, 20, 30 and 40 postpartum. The postpartum estrus interval in treated group (80.28±3.47 days) was significantly shorter (P < 0.01) as compared to control (139.00±0.91 days). The postpartum fertile estms interval in treated cows (86.43±4.01 days) was shorter (P<0.01) than that of untreated control ( 144.50±5.23 days). Significantly higher (P<0.0 1) conception rate in ’Dinoprost’ treated cows was observed as compaied to control.